Polyurethane sponge with composite structure and preparation method thereof
By using polymerization foaming technology that combines modified chitosan and modified pearl powder with polyurethane prepolymer, the bacterial breeding problem in use is solved, and the efficient antibacterial and mechanical properties of the material are improved.
Patent Information
- Application Number
- CN202411520329.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-07
AI Technical Summary
Polyurethane sponges are prone to bacterial growth during use or storage, which poses health risks, and the prior art is difficult to effectively improve their antibacterial properties.
Polyurethane prepolymer, modified chitosan and modified pearl powder are used as the main raw materials, and the antibacterial and mechanical properties of the materials are prepared by quaternized modified chitosan and carboxylated pearl powder, combined with polymerization foaming.
显著提高了聚氨酯海绵的抗菌性和力学性能,有效抑制细菌滋生,确保了材料的安全性和使用性能。
Smart Images

Figure BDA0005107873820000091 
Figure BDA0005107873820000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sponge products, and specifically relates to a polyurethane sponge with a composite structure and a preparation method thereof. Background Art
[0002] Polyurethane is a type of polymer composed of alternating soft segments and hard segments. It contains a large number of carbamate groups in the main chain of the macromolecule, which is similar to peptide bonds, so it has good biocompatibility. By selecting the appropriate types, structures and proportions of soft and hard segments, foam products with good physical and mechanical properties and good processing properties can be synthesized. Due to its good compatibility and large degree of freedom in molecular design, polyurethane materials are of various types and have a wide range of uses. However, during the use or storage of polyurethane products, they will cause bacteria to grow under suitable temperature and humidity conditions, posing a huge threat to human life and health.
[0003] The patent with application number CN202310816615.0 discloses a gel memory sponge and its preparation method. By adjusting the proportion of each component of the polyether polyol mixture, the physical properties of the gel memory sponge, such as resilience, hardness, etc., are changed. At the same time, the added silica gel powder further improves the heat absorption and heat dissipation performance of the gel memory sponge. In addition, a tin catalyst is used in the preparation process to promote the formation of a gel structure when the sponge foams, and promote the dispersion of the silica gel powder. The patent with application number CN202311113877.7 discloses a foam composition, a method for preparing polyurethane foam, and a polyurethane foam. The foam composition includes polyols, hydrofluoroolefins, flame retardants, and catalysts. The foam mixture has good environmental performance, does not damage the ozone layer, and has a low greenhouse effect potential. The prepared foam has a good flame retardant effect. However, polyurethane sponges still have the problem of internal bacterial growth and health risks during use, so how to improve the antibacterial properties of polyurethane sponges has become a focus of attention. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the present invention provides a polyurethane sponge with a composite structure and a preparation method thereof, which is prepared by polymerization and foaming of polyurethane prepolymer, modified chitosan and modified pearl powder as main raw materials. The prepared polyurethane sponge has good antibacterial and mechanical properties.
[0005] The present invention adopts the following technical solutions:
[0006] A polyurethane sponge with a composite structure comprises the following raw materials in parts by weight: 60-75 parts of a polyurethane prepolymer, 16-22 parts of modified chitosan, 8-12 parts of modified pearl powder, 0.6-1.2 parts of a foam stabilizer, 0.8-1.5 parts of a catalyst, and 0.8-1.5 parts of a foaming agent; preferably, 65 parts of a polyurethane prepolymer, 18 parts of modified chitosan, 10 parts of modified pearl powder, 0.8 parts of a foam stabilizer, 1 part of a catalyst, and 1 part of a foaming agent.
[0007] Furthermore, the foam stabilizer is L-580, the foaming agent is deionized water, and the catalyst is the organic zinc catalyst T52.
[0008] Furthermore, the preparation method of the polyurethane prepolymer is as follows: under an inert atmosphere, preferably a nitrogen atmosphere, a polyethylene glycol material is added to a reactor, stirred and heated until the material is completely dissolved, the temperature is increased to 95-105° C. for vacuum dehydration for 2-4 hours, stannous octoate is added, stirring is continued, and the temperature is lowered to 75-85° C. for reaction for 15-20 minutes, and then an N-methylpyrrolidone solution of isophorone diisocyanate is added thereto at a rate of 2-4 mL / min, and after the addition is completed, the material is placed at 80-90° C. for reaction for 1-2 hours, and then a blocking agent is added and the temperature is increased to The method comprises the steps of: reacting at 120-130°C for 2-4h, then reducing the temperature to 90-100°C for 1-2h, adding 1,4-butanediol and reacting at 85-95°C for 2-4h to obtain the product; wherein the mass ratio of polyethylene glycol, stannous octoate, isophorone diisocyanate, blocking agent and 1,4-butanediol is 80-100:1:45-58:4-5:8-12, the mass fraction of isophorone diisocyanate in the N-methylpyrrolidone solution of isophorone diisocyanate is 20%-25%; and the blocking agent is sodium pyrosulfite, sodium bisulfite or ammonium bisulfite.
[0009] Furthermore, the preparation method of the modified chitosan is as follows: dissolving chitosan in an acetic acid solution, then adding glycidyl trimethyl ammonium chloride, stirring evenly at room temperature, then adding a NaOH solution and continuing to stir and raising the temperature to 50-60° C. for reaction for 1-3 hours to obtain a viscous solid crude product, and soaking it in an ethanol solution, and adjusting the pH to neutral by adding acetic acid, soaking for 18-24 hours, and then filtering and washing with anhydrous ethanol, and extracting with anhydrous ethanol as a solvent using a Soxhlet extractor for 18 -24h and then vacuum dried at 50-60°C for 12-16h to obtain a light yellow powder product, which is the modified chitosan; wherein the mass fraction of the acetic acid solution is 1%; the mass fraction of the NaOH solution is 2%; the mass fraction of the ethanol solution is 80%; the mass ratio of chitosan and glycidyl trimethylammonium chloride is 3-5:1, the volume ratio of the acetic acid solution, the NaOH solution and the ethanol solution is 5-8:1:8-12, and the amount of chitosan added to the acetic acid solution is 0.1-0.3g / mL.
[0010] The main chain of polyurethane contains a large number of repeated carbamate groups, which are composed of soft segments and hard segments repeated alternately, wherein the soft segments constitute the continuous phase of the material, so that the material maintains a certain elasticity, while the hard segments constitute the dispersed phase of the material, so that the material maintains a certain rigidity; polyethylene glycol is a linear polymer material, which is uncharged, has good safety, good biocompatibility and solubility, can be dissolved in both water and organic solvents, and has both hydrophilicity and flexibility; in the present invention, polyethylene glycol is used as the soft segment and isophorone diisocyanate is used as the hard segment, and a prepolymer is prepared by copolymerization; polyurethane materials have been widely used due to their good compatibility and large degree of freedom in molecular design, but they can cause bacterial growth during use or storage; chitosan has a molecular structure in which N-acetylglucosamine and D-glucosamine are connected by random β (1-4) bonds, has broad-spectrum antibacterial properties, has a strong inhibitory effect on bacterial reproduction, and contains a large number of active amino groups and hydrogen atoms in its molecules. The present invention discloses a kind of chitosan with a quaternary ammonium ion. The chitosan with a quaternary ammonium ion is easy to be subjected to a variety of chemical modifications. However, in the process of chemical modification, the C2-NH2 with excellent biological activity on the chitosan structure is often used as a grafting point to participate in the reaction, resulting in a decrease or disappearance of its antibacterial property. The quaternary ammonium ion is positively charged. After the positively charged quaternary ammonium salt is adsorbed on the bacterial surface, it penetrates the cell wall and combines with the lipid layer and protein layer of the cell membrane, thereby hindering the normal ion exchange and material exchange of bacteria to the outside world, and destroying the protoplasmic membrane that controls the permeability of the cell, causing the leakage of intracellular substances and leading to bacterial death. At the same time, its hydrophobic group acts on the hydrophilic group of the microorganism to change the permeability of the membrane, thereby rupturing the microbial cell membrane and destroying the cell structure. The cationic group can also coagulate protein, denature enzymes and structural proteins, inhibit the metabolism of microorganisms, and cause the dissolution and death of cells. Therefore, in the present invention, the chitosan is firstly quaternized by using glycidyl trimethylammonium chloride to obtain quaternized chitosan, and then combined with polyurethane to improve the antibacterial property of the prepared material.
[0011] Furthermore, the preparation method of the modified pearl powder is as follows: dispersing pearl powder in a mixed solution containing citric acid and trisodium citrate, heating and drying the mixture at 80-90°C to a constant weight after ultrasonic treatment for 20-40 minutes, then raising the temperature to 100-120°C for reaction for 2-6 hours, washing and drying to obtain the modified pearl powder; wherein the preparation method of the mixed solution containing citric acid and trisodium citrate is as follows: mixing citric acid and trisodium citrate in deionized water at a mass ratio of 8:1; wherein the mass fraction of citric acid in the mixed solution is 10%; and the mass ratio of pearl powder to citric acid is 3-5:1.
[0012] Pearl powder is a powdery substance formed by crushing, grinding, processing and other processes of pearls formed by mother-of-pearl. The main components of pearl powder are calcium carbonate, protein, amino acid and various trace elements. It can generate far-infrared emission in the wavelength range of 8μm-14μm, which can not only enhance human blood circulation and metabolism, but also promote the recovery of fatigued muscles. It can be absorbed by the human body after long-term contact with the skin, and can play a good health care and anti-aging role. Since pearl powder is a powdery solid, it is easy to cause uneven dispersion when directly added during the preparation process. Therefore, in the present invention, citric acid and trisodium citrate are used to carboxylate the pearl powder, and in the subsequent preparation step, modified chitosan is used to carry out esterification reaction with carboxylated pearl powder, so that chemical bonding is formed between the pearl powder and chitosan. The presence of chitosan molecular chains can increase the steric hindrance between pearl powder particles, which is helpful to improve the dispersibility of pearl powder. In addition, the introduction of pearl powder as solid powder particles can further improve the mechanical properties of the product.
[0013] The present invention also provides a method for preparing a polyurethane sponge with a composite structure, comprising the following steps:
[0014] S1. Weigh each raw material according to the above weight parts and set aside;
[0015] S2. Using anhydrous toluene as solvent, adding modified chitosan and modified pearl powder thereto, mixing evenly, adding tetrabutyl titanate thereto and raising the temperature to 100-110°C, reacting for 2-4 hours, naturally cooling to room temperature, filtering, washing and drying to obtain solid powder; wherein the mass ratio of modified chitosan to tetrabutyl titanate is 10:1;
[0016] S3, dispersing the solid powder prepared in step S2 in an acetic acid solution, then adding a foam stabilizer and a catalyst thereto, stirring evenly, adding a foaming agent and a polyurethane prepolymer thereto, mixing evenly, adding the mixture to a mold, stirring for 15-20 seconds, curing at room temperature for 18-24 hours, and then cutting the product into standard sizes.
[0017] The present invention has the following beneficial effects:
[0018] In the present invention, polyethylene glycol is used as a soft segment, isophorone diisocyanate is used as a hard segment, and chitosan is added as a raw material through polymerization and foaming to prepare a polyurethane foam. In order to improve the antibacterial property of the polyurethane foam, chitosan is firstly quaternized by using glycidyl trimethylammonium chloride, and quaternary ammonium ions are introduced into the chitosan molecular chain. Since the quaternary ammonium ions carry a positive charge, they can be adsorbed onto the surface of the bacteria, penetrate the cell wall to hinder the normal ion exchange and material exchange between the bacteria and the outside world, and change the permeability of the cell membrane to destroy the cell structure, so that the antibacterial property of the material can be effectively improved. In addition, Pearl powder is also introduced in the preparation process. Its main components are calcium carbonate, protein, amino acids and various trace elements. Long-term contact with the skin can play a good health-care role. In the preparation process, in order to avoid uneven dispersion caused by direct addition, citric acid and sodium citrate are also used to modify the pearl powder in the present invention to form a chemical bond with chitosan. The presence of chitosan molecular chains can increase the steric hindrance between pearl powder powders and improve the dispersibility of pearl powder. In addition, the introduction of pearl powder as solid powder particles can further improve the mechanical properties of the product. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0020] The polyethylene glycol (analytical grade, MW: 2000) used in the present invention was purchased from Tianjin Jiangtian Chemical Technology Co., Ltd., stannous octoate (analytical grade) and isophorone diisocyanate (analytical grade) were purchased from Tianjin Guangfu Technology Development Co., Ltd., chitosan (analytical grade, MW: 3000) was purchased from Shanghai Yuanye Co., Ltd., glycidyl trimethylammonium chloride was purchased from Hangzhou Yanshan Chemical Co., Ltd., pearl powder (purity ≥ 99%, particle size of about 1 μm) was purchased from Zhejiang Ousiman Group Company, SBF simulated body fluid was purchased from Kangdisi Chemical (Hubei) Co., Ltd.,
[0021] The reagents used in the present invention are all commercially available.
[0022] Example 1
[0023] A polyurethane sponge with a composite structure comprises the following raw materials in parts by weight: 65 parts of polyurethane prepolymer, 18 parts of modified chitosan, 10 parts of modified pearl powder, 0.8 parts of foam stabilizer, 1 part of catalyst and 1 part of foaming agent; wherein the foam stabilizer is L-580, the foaming agent is deionized water and the catalyst is organic zinc catalyst T52.
[0024] The preparation method of the polyurethane prepolymer is as follows: under a nitrogen atmosphere, adding polyethylene glycol material into a reactor, stirring and heating until the material is completely dissolved, raising the temperature to 100°C for vacuum dehydration for 3 hours, adding stannous octoate, continuing stirring and lowering the temperature to 80°C for reaction for 20 minutes, then adding an N-methylpyrrolidone solution of isophorone diisocyanate at a rate of 3 mL / min, placing the material at 85°C for reaction for 2 hours after the addition is completed, then adding a blocking agent, sodium bisulfite, raising the temperature to 125°C for reaction for 4 hours, then lowering the temperature to 90°C for reaction for 2 hours, and then adding 1,4-butanediol for reaction at 90°C for reaction for 3 hours to obtain the prepolymer; wherein the mass ratio of polyethylene glycol, stannous octoate, isophorone diisocyanate, blocking agent, and 1,4-butanediol is 90:1:50:4:10, and the mass fraction of isophorone diisocyanate in the N-methylpyrrolidone solution of isophorone diisocyanate is 25%.
[0025] The preparation method of the modified chitosan is as follows: dissolving chitosan in acetic acid solution, then adding glycidyl trimethyl ammonium chloride, stirring evenly at room temperature, then adding NaOH solution and continuing stirring and raising the temperature to 55°C for reaction for 2 hours to obtain a viscous solid crude product, and then soaking it in an ethanol solution, and adjusting the pH to neutral by adding acetic acid, soaking for 24 hours, and then filtering and washing with anhydrous ethanol, extracting with anhydrous ethanol as a solvent with a Soxhlet extractor for 24 hours, and then vacuum drying at 55°C for 14 hours to obtain a light yellow powder product, which is the modified chitosan; wherein the mass fraction of the acetic acid solution is 1%; the mass fraction of the NaOH solution is 2%; the mass fraction of the ethanol solution is 80%; the mass ratio of chitosan and glycidyl trimethyl ammonium chloride is 4:1, the volume ratio of the acetic acid solution, the NaOH solution, and the ethanol solution is 6:1:10, and the amount of chitosan added to the acetic acid solution is 0.2 g / mL.
[0026] The preparation method of the modified pearl powder is as follows: the pearl powder is dispersed in a mixed solution containing citric acid and trisodium citrate, and after ultrasonic treatment for 30 minutes, the mixture is heated and dried at 85°C until the weight is constant, and then the temperature is increased to 110°C for reaction for 4 hours, and then the mixture is washed with deionized water, and then dried at 65°C for 2 hours to obtain the modified pearl powder; the preparation method of the mixed solution containing citric acid and trisodium citrate is as follows: citric acid and trisodium citrate are mixed in deionized water at a mass ratio of 8:1; the mass fraction of citric acid in the mixed solution is 10%; and the mass ratio of pearl powder to citric acid is 4:1.
[0027] A method for preparing a polyurethane sponge with a composite structure comprises the following steps:
[0028] S1. Weigh each raw material according to the above weight parts and set aside;
[0029] S2, using 50 parts by weight of anhydrous toluene as solvent, adding 18 parts by weight of modified chitosan and 10 parts by weight of modified pearl powder thereto, mixing evenly, adding 1.8 parts by weight of tetrabutyl titanate thereto and raising the temperature to 110°C, reacting for 3 hours, cooling naturally to room temperature, filtering out the residue, washing with deionized water, and drying at 65°C for 2 hours to obtain a solid powder;
[0030] S3, dispersing the solid powder prepared in step S2 in 100 parts by weight of acetic acid solution, then adding 0.8 parts by weight of foam stabilizer and 1 part by weight of catalyst thereto, stirring evenly, adding 1 part by weight of foaming agent and 65 parts by weight of polyurethane prepolymer thereto, mixing evenly, adding to a mold, stirring for 20 seconds, curing at room temperature for 20 hours, and then cutting the product into standard sizes; wherein the mass fraction of the acetic acid solution is 5%.
[0031] Example 2
[0032] Compared with Example 1, this embodiment has the following differences, specifically:
[0033] A polyurethane sponge with a composite structure comprises the following raw materials in parts by weight: 60 parts of polyurethane prepolymer, 16 parts of modified chitosan, 8 parts of modified pearl powder, 0.6 parts of foam stabilizer, 0.8 parts of catalyst and 0.8 parts of foaming agent.
[0034] In the preparation process of the polyurethane prepolymer, a polyethylene glycol material is added to the reactor until the material is completely dissolved, and then the temperature is raised to 95°C for vacuum dehydration for 2 hours, stannous octoate is added, stirring is continued, and the temperature is lowered to 75°C for reaction for 15 minutes, and then an N-methylpyrrolidone solution of isophorone diisocyanate is added thereto at a rate of 2 mL / min. After the addition is completed, the material is placed at 80°C for reaction for 1 hour, and then a blocking agent is added to raise the temperature to 120°C for reaction for 2 hours, and then the temperature is lowered to 90°C for reaction for 1 hour, and then 1,4-butanediol is added to react at 85°C for 2 hours; wherein the mass ratio of polyethylene glycol, stannous octoate, isophorone diisocyanate, blocking agent, and 1,4-butanediol is 80:1:45:4:8, and the mass fraction of isophorone diisocyanate in the N-methylpyrrolidone solution of isophorone diisocyanate is 20%.
[0035] During the preparation of modified chitosan, NaOH solution was added and stirring was continued, and the temperature was raised to 50°C for reaction for 1 hour, acetic acid was added to adjust the pH to neutral and then soaked for 18 hours, extracted with anhydrous ethanol for 18 hours using a Soxhlet extractor and then vacuum dried at 50°C for 12 hours; the mass ratio of chitosan to glycidyltrimethylammonium chloride was 3:1, the volume ratio of acetic acid solution, NaOH solution and ethanol solution was 5:1:8, and the amount of chitosan added to the acetic acid solution was 0.1 g / mL.
[0036] In the preparation process of the modified pearl powder, after ultrasonication for 20 minutes, it was heated and dried at 80°C to constant weight, and then the temperature was raised to 100°C for reaction for 2 hours; the mass ratio of pearl powder to citric acid was 3:1.
[0037] In the preparation process of the polyurethane sponge, in step S2, tetrabutyl titanate is added and the temperature is raised to 100° C. to react for 2 hours; in step S3, after being mixed evenly, the mixture is added to a mold and stirred for 15 seconds and then cured at room temperature for 18 hours.
[0038] Example 3
[0039] Compared with Example 1, this embodiment has the following differences, specifically:
[0040] A polyurethane sponge with a composite structure comprises the following raw materials in parts by weight: 75 parts of polyurethane prepolymer, 22 parts of modified chitosan, 12 parts of modified pearl powder, 1.2 parts of foam stabilizer, 1.5 parts of catalyst and 1.5 parts of foaming agent.
[0041] In the preparation process of the polyurethane prepolymer, a polyethylene glycol material is added to the reactor until the material is completely dissolved, and then the temperature is raised to 105° C. for vacuum dehydration for 4 hours, stannous octoate is added, stirring is continued, and the temperature is lowered to 85° C. for reaction for 20 minutes, and then an N-methylpyrrolidone solution of isophorone diisocyanate is added thereto at a rate of 4 mL / min. After the addition is completed, the material is placed at 90° C. for reaction for 2 hours, and then a blocking agent is added to raise the temperature to 130° C. for reaction for 4 hours, and then the temperature is lowered to 100° C. for reaction for 2 hours, and then 1,4-butanediol is added to react at 95° C. for 4 hours; wherein the mass ratio of polyethylene glycol, stannous octoate, isophorone diisocyanate, blocking agent, and 1,4-butanediol is 100:1:58:5:12, and the mass fraction of isophorone diisocyanate in the N-methylpyrrolidone solution of isophorone diisocyanate is 25%.
[0042] During the preparation of modified chitosan, NaOH solution was added and stirring was continued, and the temperature was raised to 60°C for reaction for 3 hours. Acetic acid was added to adjust the pH to neutral and then soaked for 24 hours. Anhydrous ethanol was used as the solvent and extracted with a Soxhlet extractor for 24 hours and then vacuum dried at 60°C for 16 hours. The mass ratio of chitosan and glycidyltrimethylammonium chloride was 5:1, the volume ratio of acetic acid solution, NaOH solution and ethanol solution was 8:1:12, and the amount of chitosan added to the acetic acid solution was 0.3 g / mL.
[0043] In the preparation process of the modified pearl powder, after ultrasonic treatment for 40 minutes, it was heated and dried at 90°C to constant weight, and then the temperature was raised to 120°C for reaction for 6 hours; the mass ratio of pearl powder to citric acid was 5:1.
[0044] In the preparation process of the polyurethane sponge, in step S2, tetrabutyl titanate is added and the temperature is raised to 110° C. to react for 4 hours; in step S3, after being mixed evenly, the mixture is added to a mold and stirred for 20 seconds and then cured at room temperature for 24 hours.
[0045] Comparative Example 1
[0046] Compared with Example 1, this comparative example does not modify the pearl powder, and the rest is referred to Example 1, as follows:
[0047] A polyurethane sponge with a composite structure comprises the following raw materials in parts by weight: 65 parts of polyurethane prepolymer, 18 parts of modified chitosan, 10 parts of pearl powder, 0.8 parts of foam stabilizer, 1 part of catalyst and 1 part of foaming agent; wherein the foam stabilizer is L-580, the foaming agent is deionized water and the catalyst is organic zinc catalyst T52.
[0048] A method for preparing a polyurethane sponge with a composite structure comprises the following steps:
[0049] S2, using 50 parts by weight of anhydrous toluene as solvent, adding 18 parts by weight of modified chitosan and 10 parts by weight of pearl powder thereto, mixing evenly, adding 1.8 parts by weight of tetrabutyl titanate thereto and raising the temperature to 110°C, reacting for 3 hours, cooling naturally to room temperature, filtering out the residue, washing with deionized water, and drying at 65°C for 2 hours to obtain a solid powder;
[0050] Steps S1 and S3 refer to steps S1 and S3 of embodiment 1.
[0051] Comparative Example 2
[0052] Compared with Example 1, this comparative example does not modify the pearl powder and chitosan, and the rest is referred to Example 1, as follows:
[0053] A polyurethane sponge with a composite structure comprises the following raw materials in parts by weight: 65 parts of polyurethane prepolymer, 18 parts of chitosan, 10 parts of pearl powder, 0.8 parts of foam stabilizer, 1 part of catalyst and 1 part of foaming agent; wherein the foam stabilizer is L-580, the foaming agent is deionized water and the catalyst is organic zinc catalyst T52.
[0054] A method for preparing a polyurethane sponge with a composite structure comprises the following steps: weighing the raw materials according to the above weight parts; dispersing chitosan and pearl powder in 100 weight parts of acetic acid solution, adding 0.8 weight parts of foam stabilizer and 1 weight part of catalyst thereto after mixing evenly, adding 1 weight part of foaming agent and 65 weight parts of polyurethane prepolymer thereto after stirring evenly, adding the mixture into a mold after mixing evenly and stirring for 20 seconds, curing at room temperature for 20 hours, and then cutting the product into standard sizes; wherein the mass fraction of the acetic acid solution is 5%.
[0055] Comparative Example 3
[0056] Compared with Example 1, this comparative example does not modify chitosan and does not add pearl powder. The rest is the same as Example 1, as follows:
[0057] A polyurethane sponge with a composite structure comprises the following raw materials in parts by weight: 65 parts of polyurethane prepolymer, 18 parts of chitosan, 0.8 parts of foam stabilizer, 1 part of catalyst and 1 part of foaming agent; wherein the foam stabilizer is L-580, the foaming agent is deionized water and the catalyst is organic zinc catalyst T52.
[0058] A method for preparing a polyurethane sponge with a composite structure comprises the following steps: weighing each raw material according to the above weight parts; dispersing chitosan in 100 weight parts of acetic acid solution, adding 0.8 weight parts of foam stabilizer and 1 weight part of catalyst thereto after mixing evenly, adding 1 weight part of foaming agent and 65 weight parts of polyurethane prepolymer thereto after stirring evenly, adding the mixture into a mold after mixing evenly and stirring for 20 seconds, curing at room temperature for 20 hours, and then cutting the product into standard sizes; wherein the mass fraction of the acetic acid solution is 5%.
[0059] Related tests:
[0060] Mechanical properties test: The prepared samples were tested for mechanical properties using an electronic universal testing machine: (1) The fully dried samples were cut into shapes with a length of 50 mm and a width of 10 mm, and stress-strain tests were performed at room temperature with a tensile rate of 5 mm / min; (2) At room temperature, the cut samples were immersed in SBF simulated body fluid for 15 min to obtain wet samples, and the surface moisture was gently wiped off with filter paper, and stress-strain tests were immediately performed with a tensile rate of 5 mm / min. The test results are shown in Table 1.
[0061] Table 1 Mechanical properties test results
[0062]
[0063]
[0064] It can be seen from the test results in Table 1 that the Young's modulus, elongation at break and tensile strength of the samples prepared in Examples 1-3 are all higher than those in Comparative Examples 1-3. It can be seen from the comparison between Example 1 and Comparative Example 1 (without modifying the pearl powder) that after the surface of the pearl powder is carboxylated, it is combined with the modified chitosan through chemical bonds, which can effectively improve the dispersibility of the pearl powder among the materials in the subsequent preparation process, thereby improving the mechanical properties of the prepared product.
[0065] Antibacterial performance test: Add the prepared E. coli liquid to the LB medium at a temperature of about 45°C, shake it well and pour it into the culture dish, let it stand for 10 minutes, and wait for it to cool and solidify for use. Then use tweezers to put the cut samples with a diameter of about 5mm (which have been sterilized by ultraviolet light) into the culture medium coated with the liquid, and put a polyurethane sponge (purchased from Ruian Fangyuan Polyurethane Co., Ltd.) in each culture dish as a blank control. The antibacterial condition of each sample is tested by observing the size of the antibacterial circle. The test results are shown in Table 2.
[0066] Table 2 Antibacterial test results
[0067] Group Inhibition zone (mm) Example 1 3.5 Example 2 3.3 Example 3 3.2 Comparative Example 1 2.8 Comparative Example 2 2.2 Comparative Example 3 2.0 Blank control group 0
[0068] From the test results in Table 2, it can be seen that the antibacterial effects of Examples 1-3 are better than those of Comparative Examples 1-3, especially the antibacterial effect of Example 1 is the best. By comparing Comparative Example 3 (no modification of chitosan and no addition of pearl powder) with the blank control group, it can be found that the addition of chitosan has a certain antibacterial effect. By further comparing Example 1, Comparative Example 1 (no modification of pearl powder) and Comparative Example 2 (no modification of pearl powder and chitosan), it can be seen that the quaternary ammonium modification of chitosan can produce obvious antibacterial circles for the experimental bacteria, indicating that the quaternary ammonium modification of chitosan has good antibacterial performance against Escherichia coli.
[0069] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0070] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A polyurethane sponge with a composite structure, characterized in that: The invention comprises the following raw materials in parts by weight: 60-75 parts of polyurethane prepolymer, 16-22 parts of modified chitosan, 8-12 parts of modified pearl powder, 0.6-1.2 parts of foam stabilizer, 0.8-1.5 parts of catalyst and 0.8-1.5 parts of foaming agent.
2. The polyurethane sponge with a composite structure according to claim 1, characterized in that: The preparation method of the polyurethane prepolymer comprises the following steps: adding polyethylene glycol material into a reactor under an inert atmosphere, stirring and heating until the material is completely dissolved, raising the temperature to 95-105° C. for vacuum dehydration for 2-4 hours, adding stannous octoate, continuing stirring and lowering the temperature to 75-85° C. for reaction for 15-20 minutes, then adding an N-methylpyrrolidone solution of isophorone diisocyanate thereto, placing the material at 80-90° C. for reaction for 1-2 hours after the addition is completed, then adding a capping agent, raising the temperature to 120-130° C. for reaction for 2-4 hours, then lowering the temperature to 90-100° C. for reaction for 1-2 hours, and then adding 1,4-butanediol for reaction at 85-95° C. for reaction for 2-4 hours to obtain the polyurethane prepolymer.
3. The polyurethane sponge with a composite structure according to claim 1, characterized in that: The preparation method of the modified chitosan is as follows: dissolving chitosan in an acetic acid solution, then adding glycidyl trimethylammonium chloride, stirring evenly at room temperature, then adding a NaOH solution, continuing to stir and raising the temperature to 50-60° C. for reaction for 1-3 hours to obtain a viscous solid crude product, and soaking the crude product in an ethanol solution, and adjusting the pH to neutral by adding acetic acid, soaking for 18-24 hours, and then filtering and washing with anhydrous ethanol, extracting with anhydrous ethanol as a solvent with a Soxhlet extractor for 18-24 hours, and then vacuum drying to obtain a light yellow powder product, namely the modified chitosan.
4. The polyurethane sponge with a composite structure according to claim 1, characterized in that: The preparation method of the modified pearl powder is as follows: dispersing the pearl powder in a mixed solution containing citric acid and trisodium citrate, heating and drying the mixture at 80-90° C. to a constant weight after ultrasonic treatment for 20-40 minutes, then raising the temperature to 100-120° C. to react for 2-6 hours, and obtaining the modified pearl powder after washing and drying.
5. The polyurethane sponge with a composite structure according to claim 2, characterized in that: The rate of addition of the isophorone diisocyanate solution in N-methylpyrrolidone was 2-4 mL / min.
6. The polyurethane sponge with a composite structure according to claim 2, characterized in that: The mass fraction of isophorone diisocyanate in the N-methylpyrrolidone solution of isophorone diisocyanate is 0.4%-0.8%.
7. The polyurethane sponge with a composite structure according to claim 2, characterized in that: The end-capping agent is sodium pyrosulfite, sodium bisulfite or ammonium bisulfite.
8. The polyurethane sponge with a composite structure according to claim 3, characterized in that: The vacuum drying conditions are: 50-60°C for 12-16 hours.
9. The method for preparing a polyurethane sponge with a composite structure according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Weigh each raw material according to the above weight parts and set aside; S2, using anhydrous toluene as solvent, adding modified chitosan and modified pearl powder thereto, mixing evenly, adding tetrabutyl titanate thereto and raising the temperature to 100-110°C, reacting for 2-4 hours, naturally cooling to room temperature, filtering, washing and drying to obtain a solid powder; S3, dispersing the solid powder prepared in step S2 in an acetic acid solution, then adding a foam stabilizer and a catalyst thereto, stirring evenly, adding a foaming agent and a polyurethane prepolymer thereto, mixing evenly, adding the mixture to a mold, stirring for 15-20 seconds, curing at room temperature for 18-24 hours, and then cutting the product into standard sizes.
Citation Information
Patent Citations
Gel memory sponge and preparation method thereof
CN116693792A
Foam composition, method for preparing polyurethane foam, and polyurethane foam
CN116836355B
Cited By
Coating material, preparation method and application in trace element coating for potassium chloride particles
CN120117933A
Chitosan-polyurethane composite hemostatic sponge and preparation method therefor
WO2026199786A1